Retention rate of physicians in public health administration agencies and their career paths in Japan - Yasunaga Hideo; Ide Hiroo; Matsumoto Shinya; Kodama Tomoko; Koike Soichi; Imamura Tomoaki (BMC, 2010)
Abstract Background Physicians who serve as public health specialists at public health centers and health departments in local or central government have significant roles because of their public health expertise. The aim of this study is to analyze the retention and career paths of such specialists in Japan. Method We analyzed the data of seven consecutive surveys, spanning 1994 to 2006. We first analyzed the 2006 survey data by sex, age group, and facility type. We then examined the changes over time in the proportion of physicians working in public health administration agencies. We also examined the distribution of the facility types and specialties in which physicians worked both before beginning and after leaving their jobs. These analyses were performed by using physician registration numbers to cross-link data from two consecutive surveys. Results The proportion of physicians working in public health administration agencies was 0.7% in 2006. The actual numbers for each survey ranged between 1,800 and 1,900. The overall rate remaining in public health administration agencies during the two-year survey interval was 72.8% for 1994-1996. The ratio declined to 67.2% for 2004-2006. Among younger physicians with 1-10 years of experience, the retention rate showed a sharp decline, dropping from 72.6% to 50.0%. Many of these physicians came from or left for a hospital position, with the proportion entering academic hospital institutions increasing in recent years. In many cases, physicians left or entered internal medicine clinical practices. Conclusion At present in Japan, the number of physicians who leave and the number who begin a position are almost the same; thus, some of the problems associated with physicians leaving are yet to become apparent. However, the fact that the retention period is shortening for younger physicians may represent a future problem for ensuring the quality of physicians in public health administration agencies. Possible strategies include: increasing the number of physicians entering positions; reducing the number leaving positions; and creating a system where physicians can easily reenter positions after leaving while also establishing a revolving door type of career development system, involving both public health departments and hospital clinical departments.